Factors that influence students in choosing Institut Profesional Baitulmal as their private higher education institution / Muhammad Aizat Zulkipli - Zulkipli, Muhammad Aizat (2017)
Purpose — This is to identify the factors that influence students in choosing Institut Profesional Baitulmal as the private higher education institution. For this research, the researcher examine three factors that is perception of brand image, facilities provided and course offer. This study is to help the company improve on the factors that can attract students towards the institution.